Little Bobo - Romanelli, Serena (New York : North-South Books, 1995)
When a strange object falls off a truck passing through the jungle, a bored orangutan discovers that he can make a wonderful sounds with it and in times his family and other jungle animals come to appreciate music well.
Keywords: Orangutan -- Fiction; Music -- Fiction; Violin -- Fiction